2019
DOI: 10.1111/ijcs.12546
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Spanish consumers towards environmentally friendly labelling in food

Abstract: Food consumption is one of the most important areas to influence environmental sustainability since it is responsible for one third of a household's total environmental impact. However, many consumers are not completely aware of the association between their food consumption and the environmental consequences. Recently, some food companies have developed labelling schemes to help inform their consumers of the impact a specific food product has on the environment during its production. The main objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
64
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 68 publications
4
64
1
Order By: Relevance
“…Unlike previous research documenting a gap between general environmental knowledge and pro‐environmental behaviours (e.g., Eldesouky, Mesias, & Escribano, 2020; Frederiks, Stenner, & Hobman, 2015; Grimmer & Miles, 2017; Kollmuss & Agyeman, 2002; Paço & Lavrador, 2017; Steg, Perlaviciute, & van der Werff, 2015; Torma, Aschemann‐Witzel, & Thøgersen, 2018), the focus of this study is on the relationship between a narrow knowledge of electricity use and consumption, which is mainly driven by concrete financial motives (rather than altruistic values), and actual electricity savings (Blasch et al., 2017; Brounen et al., 2013; Trotta, Kalmi, & Kazukauskas, 2017). Awareness of electricity use and consumption, being one component of “energy literacy”, was found to be correlated with “financial literacy”, savvy financial choices and lower electricity consumption (Blasch et al., 2017).…”
Section: Theoretical Framework and Hypothesescontrasting
confidence: 66%
“…Unlike previous research documenting a gap between general environmental knowledge and pro‐environmental behaviours (e.g., Eldesouky, Mesias, & Escribano, 2020; Frederiks, Stenner, & Hobman, 2015; Grimmer & Miles, 2017; Kollmuss & Agyeman, 2002; Paço & Lavrador, 2017; Steg, Perlaviciute, & van der Werff, 2015; Torma, Aschemann‐Witzel, & Thøgersen, 2018), the focus of this study is on the relationship between a narrow knowledge of electricity use and consumption, which is mainly driven by concrete financial motives (rather than altruistic values), and actual electricity savings (Blasch et al., 2017; Brounen et al., 2013; Trotta, Kalmi, & Kazukauskas, 2017). Awareness of electricity use and consumption, being one component of “energy literacy”, was found to be correlated with “financial literacy”, savvy financial choices and lower electricity consumption (Blasch et al., 2017).…”
Section: Theoretical Framework and Hypothesescontrasting
confidence: 66%
“…Packaging, especially front‐of‐package labelling, largely shapes consumers' first impressions of a product. Different verbal statements, symbols and logos endorse specific properties of the product—for example, environmental concerns attract consumers' attention and help raise the product's reliability for them, thereby increasing their trust in it (Eldesouky, Mesias, & Escribano, 2020; Taufique, Polonsky, Vocino, & Siwar, 2019). Some studies have indicated that visual elements can enhance the communication effectiveness and are more important than verbal information (Carrillo, Fiszman, Lähteenmäki, & Varela, 2014); in others (Klopčič, Slokan, & Erjavec, 2020), consumers revealed that the importance of verbal claims is greater than that of images.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…Voordouw, Cornelisse-Vermaat, and Pfaff (2011, p. 385) conclude that "current food allergy coping strategies adopted by consumers are inadequate", though, as they mostly revolve around restricting "dietary choices" based on food labels, largely ignoring aspects such as aesthetics and pleasure. Eldesouky, Mesias, and Escribano (2020) have shown that food labels alone are insufficient to markedly affect consumption behaviour in the context of sustainable food consumption. Some coping strategies aim at destigmatization: Sandikci and Ger (2010) analyse how the practice of veiling in Turkey has been routinized and, consequently, destigmatized, while Scaraboto and Fischer (2013) study the phenomenon of "Fatshionistas", showing how marginalized consumers fight stigma and seek for greater inclusion in the marketplace.…”
Section: Social Stigma and Coping Strategiesmentioning
confidence: 99%